TECHNOLOGICALLY OR ECONOMICALLY OPTIMAL MICROWAVE DRYING OF BULK FEED - Dubrovin, A. (Energy and Automation, 2016)
Designed for installation of microwave drying of bulk feed. Production is carried out in automatic mode according to technological or economic criteria.